HPV circulating tumoral DNA quantification by droplet‐based digital PCR: A promising predictive and prognostic biomarker for HPV‐associated oropharyngeal cancers. Issue 4 (18th December 2019) - Veyer, David; Wack, Maxime; Mandavit, Marion; Garrigou, Sonia; Hans, Stéphane; Bonfils, Pierre; Tartour, Eric; Bélec, Laurent; Wang‐Renault, Shu‐Fang; Laurent‐Puig, Pierre; Mirghani, Haitham; Rance, Bastien; et al.
Abstract : We aimed to determine whether pretherapeutic assessment of HPV circulating tumoral DNA (HPV ctDNA) by droplet‐based digital PCR (ddPCR) could constitute a predictive and prognostic biomarker for HPV‐associated oropharyngeal squamous cell carcinoma (OPSCC). A mono‐institutional prospective biomarker study on 66 patients with p16+/HPV16‐positive oropharyngeal squamous cell carcinoma (OPSCC) was conducted in European Georges Pompidou Hospital, Paris, France. Blood samples were collected at the time of diagnosis before any treatment. Optimized digital PCR assays were used to quantify HPV16 ctDNA. Forty‐seven (71%) patients showed a positive pretherapeutic HPV ctDNA at time of diagnosis. Interestingly, the quantity of HPV16 ctDNA at baseline, as assessed by ddPCR, was significantly correlated with the T/N/M status or OPSCC stages according to the 2018 new staging criteria for high‐risk human papillomavirus (HR HPV) related OPSCC from American Joint Committee on Cancer (AJCC). Moreover, all recurrences and the majority (83%) of death reported events occurred in patients with positive HPV16 ctDNA at baseline. Finally, when posttreatment blood samples were available ( n = 6), the kinetic of pretreatment/posttreatment HPV16 ctDNA was clearly associated with treatment success or failure. HPV ctDNA monitoring by ddPCR could constitute a useful and noninvasive dynamic biomarker to select HR HPV‐related OPSCC patients eligible for potential treatment de‐escalation and to monitor treatment response. Abstract : What's new? Circulating tumor DNA represents a tantalizing avenue for non‐invasive diagnostic and prognostic testing. Here, the authors investigated whether HPV16 ctDNA correlated with disease stage and outcome in oropharyngeal squamous cell carcinoma (OPSCC). Using digital PCR, they tested 66 blood samples collected at diagnosis, before treatment began. 71% of the patients tested positive for HPV ctDNA, and those patients tended to have more advanced disease than those with undetectable HPV ctDNA. Outcomes also appeared linked with the marker, as 83% of deaths occurred among patients with HPV ctDNA. Finally, post‐treatment assessment of ctDNA levels in 6 patients correlated with treatment response.